A cultural integration path for cross-border mergers and acquisitions from the perspective of acculturation: a double case study. Issue 3 (1st August 2016) - Cui, Miao; Dung, Jiawei; Liu, Yuekun; Wang, Shujuan
Abstract : Purpose: An increasing number of Chinese enterprises are involved in cross-border mergers and acquisitions (M&As). However, few Chinese enterprises have achieved successful integration, which plays a critical role in enhancing performance. The important field of cultural integration is currently facing major challenges. To identify the reasons for these challenges, studies have analyzed why cultural integration succeeds or fails and have suggested that cultural differences between acquiring and acquired enterprises are the primary obstacles to cultural integration. However, it is unclear how success can be achieved. We focus on cultural integration from the perspective of acculturation to describe the penetration of cultural elements in M&As. Design/methodology/approach: In adopting acculturation as our theoretical lens, we use the case study method to answer the following research question: "how can the cultural integration of Chinese enterprises be successfully achieved?" Two typical cases are examined: Lenovo's cultural integration with IBM's PC Division and Haier's cultural integration with Sanyo Home Appliance. First, using the exploratory case study method, the Lenovo-IBM PC Division case is analyzed. The characteristics and relationships between cultural environments, employee adoption methods and acculturation patterns are summarized to reveal a cultural integration path. Second, the Haier-Sanyo Home Appliance case is analyzed using the confirmative case study method to test the findings of the Lenovo-IBM PC Division case. Findings: Our results indicate that it is critical to achieve a dynamic fit between cultural environments, employee adoption methods and acculturation patterns during each stage of cultural integration (exploration, experimentation, reinforcement and fixing). The three constructs of these stages reflect the following evolutionary paths: "isolate-introduce-learning-chance taking, " "detecting-icebreaking-interacting-remodeling, " and "specialized sections-senior managers-managers-employees." Originality/value: These findings contribute to the development of cultural integration and acculturation theories and serve as a reference for Chinese enterprises wishing to implement cultural integration strategies.